Attentional Resource Associated With Visual Feedback on a Postural Dual Task in Parkinson's Disease. (October 2020) - Yu, Shu-Han; Wu, Ruey-Meei; Huang, Cheng-Ya
Background: Restricted attentional resource and central processing in patients with Parkinson's disease (PD) may reduce the benefit of visual feedback in a dual task. Objectives: Using brain event-related potentials (ERPs), this study aims to investigate the neural mechanisms of posture visual feedback and supraposture visual feedback during performing of a posture-motor dual task. Methods: Eighteen patients with PD and 18 healthy controls stood on a mobile platform (postural task) and executed a manual force-matching task (suprapostural task) concurrently with provided visual feedback of platform movement (posture-feedback condition) or force output (force-feedback condition). The platform movement, force-matching performance, and ERPs (P1, N1, and P2 waves) were recorded. Results: Both PD and control groups had superior force accuracy in the force-feedback condition. Decreased postural sway by posture-feedback was observed in healthy controls but not in PD. Force-feedback led to a greater frontal area N1 peak in PD group but smaller N1 peaks in control group. In addition, force-feedback led to smaller P2 peaks of the frontal and sensorimotor areas among PD patients but greater P2 peaks of the sensorimotor and parietal-occipital areas among healthy controls. However, P1 modulations was present only in healthy controls. Conclusions: Force-feedback had positive effect on force accuracy in both PD and healthy individuals; however, the beneficial effect of posture-feedback on posture balance is not observed in PD. These findings are the first to suggest that PD could recruit more attentional resources in dual-task preparation to enhance suprapostural accuracy and avoid degrading postural stability by supraposture visual feedback.